Exploration about Beliefs of God through Cordiality of the Good Samaritan Parable and Homoousios of Nicaea Council - Xalastinus Jasper Hanta; Samuel Pella (Fakultas Teologi, Universitas Sanata Dharma, 2025)
Discussing the Parable of the Good Samaritan, one of the main themes that can be discussed is the theology of cordiality